Impact of emergency department arrival time on door-to-needle time in patients with acute stroke - Ganti, Latha; Mirajkar, Amber; Banerjee, Paul; Stead, Tej; Hanna, Andrew; Tsau, Joshua; Khan, Mohammed; Garg, Ankur (Frontiers in Neurology, 2023)
Background This study aimed to identify which emergency department (ED) factors impact door to needle time (DTN) in acute stroke patients eligible for intravenous thrombolysis. Methods This was a prospective observational quality registry that included all patients that received alteplase for stroke. The time of patent arrival to the ED was captured via the timestamp in the electronic health record. Arriving between Friday 6pm-Monday 6am was classified as “weekend,” regardless of time of arrival. Time to CT, time to lab and presence of a dedicated stroke team were also recorded. Emergency Medical Services (EMS) run sheets were used to verify arrival via ambulance. Results On univariate analyses, arriving on Night shift (P<0.0001) arriving as a walk-in (P=0.0080) and longer time to CT (P<0.0001) were associated with longer DTN. Conversely, the presence of a dedicated stroke team was associated with a significantly shorter DTN (P<0.0001). The predicted DTN time was determined by the formula: 48.5 minutes + 18.1 minutes (if the patient is a walk-in) + the value for shift time. Values for shift time were: -16.0 minutes if day shift, +15.3 minutes if night shift, and +0.6 minutes if weekend shift. Both the shift type (p <.0001) and arrival by walk-in (p =.0095) were statistically significant. This multivariate model was robust with an adjusted correlation coefficient of R2= 28.1% Conclusion Factors that contribute most to delay in DTN include arrival during the night shift, lack of dedicated stroke team, longer time to CT read, and arrival as a walk in.